Effect of Two Therapies: Compassion-Focused and Positive-Oriented on the Body Image among Female Adolescents with a History of Self-Injury - Fatemeh Kashanian; Anahita Khodabakhshi-Koolaee; Davood Taghvaei; Ghoudsi Ahghar (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Self-injury in adolescents refers to intentional behaviors that are not extrinsically motivated or do not have pre-determined intentions and impose costs on one's body image. Objectives: This study aimed to compare the effectiveness of compassion-focused therapy and positive-oriented therapy on the body image of female adolescents with a history of self-injury. Methods: This semi-experimental study with a pre-test-post-test design was conducted on 45 female high school students in district 4 of Tehran in the year of 2021. Participants were randomly divided into three groups (two intervention groups and one control group). The data were collected using a demographic information checklist and the Multidimensional Body-Self Relations Questionnaire-Appearance Scale (MBSRQ-AS) developed by Cash et al. (2000). The collected data were analyzed through multiple analysis of variance (MANCOVA) with SPSS software 26. Results: The data revealed a statistically significant difference between the mean body image and the sub-scales scores in the three groups after the intervention appearance (F=18.37; P=0.001; Eta=0.620), appearance orientation (F=0.99; P=0.001; Eta=0.599), body areas satisfaction (F=11.87; P=0.001; Eta=0.659), fitness orientation (F=15.68; P=0.001; Eta=0.603), preoccupation with weight (P =23.04; P=0.001; Eta=0.540), and body satisfaction (F=16.69; P=0.001; Eta=0.613). The Bonferroni post hoc test showed no significant difference in the effectiveness of two therapies in the participants' body image (P>0.05). Conclusion: Considering the effectiveness of both compassion-focused and positive-oriented interventions on the body image, it is suggested that these interventions be used in female adolescents with a history of self-injury to reduce anxiety and improve mental well-being.